Genes Linked to Endometriosis by GWAS Are Integral to Cytoskeleton Regulation and Suggests That Mesothelial Barrier Homeostasis Is a Factor in the Pathogenesis of Endometriosis. (June 2017) - Albertsen, Hans M.; Ward, Kenneth
Endometriosis, defined by the presence of ectopic endometrial lesions, is a common disease in reproductive-age women that profoundly affects patients' quality of life. Various pathogenic models have been proposed, but the origin of endometriosis remains elusive. In this article, we propose that the mesothelial barrier, which protects the underlying stroma from endometrial transplants present in retrograde menstrual fluid, can be compromised by activation of the epithelial to mesenchymal transition (EMT) repair mechanism that lead to temporary loss of barrier integrity. Absent of the mesothelial barrier, endometrial cells can more readily adhere to the underlying peritoneal stroma and establish endometrial lesions. The hypothesis is based on the clinical and experimental observations that correlate the location of endometrial lesions with areas of mesothelial damage, together with genetic evidence that 4 genes associated with endometriosis are direct regulators of the actin-cytoskeleton, which coordinates mesothelial barrier integrity. It supports past observations that implicate the peritoneum in the pathogenesis of endometriosis and unifies previously disparate theories that endometriosis may be triggered by infection, mechanical damage, and inflammation since each of these mechanisms can induce EMT in the mesothelium. If the hypothesis is correct, inhibition of EMT in the mesothelial barrier provides a novel paradigm for the prevention and treatment of endometriosis.